Pengaruh Pelatihan dan Pengembangan terhadap Kompetensi Karyawan - Ardhi Gigeh Pranowo; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine the effect of training and development on the competence of employees Moh. Hatta Islamic Elementary School, Malang City. The population in this study 43 employees of SD Islam Moh. Hatta City of Malang. Technical analysis used is multiple linear regression analysis. Based on the results of the study showed that training and development simultaneously had a significant effect on the competence employees of SD Islam Moh. Hatta City of Malang. Training has a significant effect on the competence employees of SD Islam Moh. Hatta City of Malang. Development has a significant effect on the competence employees of SD Islam Moh. Hatta City of Malang. Keywords : Training, Development, and Competence